A point mutation in the [2Fe–2S] cluster binding region of the NAF‐1 protein (H114C) dramatically hinders the cluster donor properties. (1st June 2014) - Tamir, Sagi; Eisenberg‐Domovich, Yael; Conlan, Andrea R.; Stofleth, Jason T.; Lipper, Colin H.; Paddock, Mark L.; Mittler, Ron; Jennings, Patricia A.; Livnah, Oded; Nechushtai, Rachel
<x xml:space="preserve">Abstract</x> NAF‐1 is an important [2Fe–2S] NEET protein associated with human health and disease. A mis‐splicing mutation in NAF‐1 results in Wolfram Syndrome type 2, a lethal childhood disease. Upregulation of NAF‐1 is found in epithelial breast cancer cells, and suppression of NAF‐1 expression by knockdown significantly suppresses tumor growth. Key to NAF‐1 function is the NEET fold with its [2Fe–2S] cluster. In this work, the high‐resolution structure of native NAF‐1 was determined to 1.65 Å resolution (R factor = 13.5%) together with that of a mutant in which the single His ligand of its [2Fe–2S] cluster, His114, was replaced by Cys. The NAF‐1 H114C mutant structure was determined to 1.58 Å resolution (R factor = 16.0%). All structural differences were localized to the cluster binding site. Compared with native NAF‐1, the [2Fe–2S] clusters of the H114C mutant were found to (i) be 25‐fold more stable, (ii) have a redox potential that is 300 mV more negative and (iii) have their cluster donation/transfer function abolished. Because no global structural differences were found between the mutant and the native (wild‐type) NAF‐1 proteins, yet significant functional differences exist between them, the NAF‐1 H114C mutant is an excellent tool to decipher the underlying biological importance of the [2Fe–2S] cluster of NAF‐1 in vivo.